Pengaruh Lingkungan Keluarga dan Minat Belajar Terhadap Kemampuan Berhitung Pecahan Siswa Kelas Atas SD Negeri 1 Taruban Nogosari Boyolali Tahun Ajaran 2015/2016 - Puspita Sari, Desi, Drs. Suwarno, SH. M.Pd (2016)
The purpose of this study was to determine include: 1) effect of the family environment against to the ability to count fractions class students of SD Negeri 1 Taruban Nogosari Boyolali academic year 2015/2016, 2) effect of the interest of student learning against to the ability to count fractions class students of SD Negeri 1 Taruban Nogosari Boyolali academic year 2015/2016, 3) to know the effect of the family environment and the interest of student learning against to the ability to count fractions class students of SD Negeri 1 Taruban Nogosari Boyolali academic year 2015/2016. The type of research based on the quantitative approach with the types of experimental studies. Data analysis technique that is used is a double linier regression test, t test and f. Based on the results of the data analysis: 1) equation regression coefficient obtained Y=-106,975+1,302 X1+ 1,081 X2. 2) Test Results t Family Environment 0,027< 0.05, family environment positive effect to the ability to count fractions students. 3) interest learn a positive effect to the ability to count fractions students, this is based on the test results t 0.039< 0.05. 4)The test results f the value of the significance of 0,003 <0.05, means family environment and interest in learning with a positive effect to the ability to count fractions class students of SD Negeri 1 Taruban Nogosari Boyolali Academic Year 2015/2016.